Dual-tasking impacts gait, cognitive performance, and gaze behavior during walking in a real-world environment in older adult fallers and non-fallers - Zukowski, A. Lisa; Tennant, E. Jaclyn; Iyigun, Gozde; Giuliani, A. Carol; Plummer, Prudence (Pergamon-Elsevier Science Ltd, 2021)
Introduction: Everyday walking often involves simultaneous performance of a cognitive task in environments with competing auditory and visual stimuli. Previous research has not evaluated task performance in these situations, where older adults are known to fall, limiting our understanding of how older adults adjust their gait, visual scanning (gaze), and cognitive processing to avoid falls (or not). The purpose of this study was to examine the effect of dual-task walking in a high-distraction real-world environment on cognitive performance, gait performance, and gaze behavior in older adult fallers relative to non-fallers. Methods: Fourteen community-dwelling, older adult fallers (76.6 +/- 9.1 years, 11 females) and 15 communitydwelling, older adult non-fallers (77.4 +/- 7.6 years, 11 females) participated. Participants performed singletask walking, single-task cognitive (seated category naming), and dual-task walking (category naming + walking) trials for 1 min each in a real-world environment (busy hospital lobby). Gait speed, stride length variability, stride duration variability, gaze fixation duration on 6 areas of interest (AOIs), and percentage of time fixating on 6 AOIs were recorded during single- and dual-task walking trials. Number of correct responses, time to first response, and mean subsequent response time (measure of rate of decline of response retrieval throughout trial) were determined for single-task cognitive and dual-task walking trials. Two-way MANCOVAs and MANOVAs were used to compare the effects of fall status and task condition on gait and cognitive variables. Hierarchical linear regression models were used to assess predictors of gaze behavior variables. Results: Compared to single-task, during dual-task trials, participants walked 0.21 m/s slower, had 1.5 fewer verbal responses, and a 2823 ms shorter mean subsequent response time, indicating a faster declining rate of retrieval during the cognitive task. Additionally, during dual-task walking, participants fixated their gaze on Far People (AOI) for a significantly smaller percentage of time and on the Near Walking Path (AOI) for a significantly greater percentage of time than during single-task walking. During all trials, being a non-faller predicted a longer average fixation duration on the Far Environment (AOI) than for fallers. Environmental busyness, baseline gait speed, and baseline executive function impacted gaze behavior. Conclusion: All participants exhibited dual-task decrements in gait and cognitive performance and changes in gaze behavior from single- to dual-task walking. Perhaps of more importance, non-fallers appear to have had more freedom to divert their gaze to less relevant environmental stimuli while walking, and two measures of fall risk impacted patterns of gaze behavior differently. Thus, overt visual attention during walking in real-world environments should be further explored in relation to fall risk.
Keywords: Aged; Accidental falls; Dual-task gait; Visual attention; Cognition